On the recovery of disorders of consciousness under intrathecal baclofen administration for severe spasticity—An observational study. Issue 5 (10th April 2022) - Halbmayer, Lucas‐Michael; Kofler, Markus; Hitzenberger, Gabriel; Matzak, Heinrich; Fava, Elena; Genelin, Eleonora; Werkmann, Mario; Saltuari, Leopold; Versace, Viviana; Dobesberger, Judith; Pucks‐Faes, Elke
Abstract: Background: Occasionally, patients show dramatic recovery from disorders of consciousness (DOC) under intrathecal baclofen (ITB), an established treatment option for severe supraspinal spasticity. Anecdotal explanations for ITB‐related recovery of cognition include modulation of afferent impulses at the spinal level, thereby reducing spasticity‐related proprioceptive information overload within cortico–thalamo–cortical connections. Objective: In this retrospective patient chart analysis, we assessed whether a reduction in spasticity would be associated with an increase in Coma Recovery Scale revised (CRS‐R) scores in a larger sample of patients than previously published. Methods: From a hospital‐based ITB treatment register, we extracted data from 26 patients with DOC and severe supraspinal spasticity who improved by >2 points on the Coma Recovery Scale revised (CRS‐R) within 6 months after ITB treatment initiation. We assessed Modified Ashworth scale (MAS) scores and CRS‐R scores on admission (PRE) and 3 and 6 months after initiation of ITB treatment (3M, 6M). We performed correlation analysis of the scores and their respective changes (PRE to 3M, 3M to 6M). We also correlated the time from acute event until ITB initiation to CRS‐R scores at 3M and 6M. Results: ITB led to significant improvement in spasticity based on MAS scores, which did not correlate to the improvements seen in CRS‐R total and subscale scores. Daily ITB dose did neither correlate to MAS scores nor to CRS‐total scores in the whole patient group, but after 3 months, ITB dose correlated to some CRS‐R subscale scores in some patient subgroups. Time until ITB treatment did not correlate to CRS‐R scores later on. Conclusions: Our data confirm that ITB may exert beneficial effects in selected DOC patients with respect to improved cognitive functions, which, however, do not correlate to its antispastic effect. The lack of correlation between time to ITB and CRS‐R outcome, but significant CRS‐R improvements following pump implantation, renders spontaneous remissions unlikely and leaves room for alternative pharmacological mechanisms. Abstract : In this retrospective patient chart analysis, we assessed whether a reduction in spasticity would be associated with an increase in Coma Recovery Scale revised (CRS‐R) scores in a larger sample of patients than previously published. Our data confirm that ITB may exert beneficial effects in selected DOC patients with respect to improved cognitive functions, which, however, do not correlate to its antispastic effect. The lack of correlation between time to ITB and CRS‐R outcome, but significant CRS‐R improvements following pump implantation, renders spontaneous remissions unlikely and leaves room for alternative pharmacological mechanisms.